PENGARUH KOMUNIKASI TERHADAP EFEKTIVITAS KERJA PEGAWAI DI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SUMEDANG - Dadang Suryana (FISIP Universitas Sebelas April, 2022)
An issue related to waste and waste management is a problem that is getting more complicated from day to The purpose of this study was to determine communication and employee work effectiveness, to determine the relationship between communication and employee work effectiveness and to determine the magnitude of the effect of communication on employee work effectiveness at the Manpower and Transmigration Office of Sumedang Regency. This study uses descriptive analysis method with a quantitative approach and the type of statistics used is descriptive statistics with probability sampling technique. The number of samples studied were 33 respondents. The analysis used includes percentage calculation, correlation test, significant test and coefficient of determination test. Based on the results of the study, it is known that the Communication in the Manpower and Transmigration Office of Sumedang Regency is in good criteria with the results of the analysis reaching 80.82%. Likewise, the Work Effectiveness of Employees at the Department of Manpower and Transmigration in Sumedang Regency is also in good criteria with the results of the analysis reaching 77.38%. From the correlation analysis, a correlation value of 0.63 can be found which indicates a positive and significant relationship between communication and the work effectiveness of employees at the Department of Manpower and Transmigration. From the results of the significance test, the t-count value is greater than the t-table, namely 4.496 > 2.039. From the analysis of the coefficient of determination, it is known that the communication variable has an influence on the work effectiveness of employees by 39.81%.